Effects of moisture absorption and surface modification using 3-aminopropyltriethoxysilane on the tensile and fracture characteristics of MWCNT/epoxy nanocomposites - Lee, J.H.; Rhee, K.Y.; Lee, J.H.
In this study, we examined the tensile and fracture behaviors of multi-walled carbon nanotube (MWCNT)reinforced epoxy nanocomposites with and without moisture absorption. The MWCNT/epoxy nanocomposites were fabricated using 0.1 wt.
Keywords: MULTI-WALLED CARBON NANOTUBES (MWCNTS); MOISTURE ABSORPTION; SURFACE MODIFICATION; TENSILE STRENGTH; FRACTURE TOUGHNESS